2016
DOI: 10.1007/s12011-016-0839-4
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Blood Lead, Cadmium, Zinc and Copper in Development and Severity of Acne Vulgaris in a Nigerian Population

Abstract: Acne vulgaris is a very common skin disorder affecting human beings. There is a paucity of report on the role of heavy metals-lead (Pb) and cadmium (Cd)-globally, and trace metals-zinc (Zn) and copper (Cd)-particularly in Nigeria in the development/severity of acne vulgaris. This study is aimed to determine the blood levels of some heavy metals-cadmium and lead-and trace metals-zinc and copper-in acne vulgaris sufferers in a Nigerian population. Venous blood samples were collected from a total number of 90 non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
0
11
1
Order By: Relevance
“…There were 12 randomized controlled trials and 13 prospective observational studies from 13 countries in Europe, Asia, the Middle East, Africa, and the United States. A total of 12 studies provided data regarding mean serum zinc levels in acne and controls (Table 1), [8][9][10][11][12][13][14][15][16][17][18][19] while 13 studies provided data regarding the efficacy of zinc therapy compared to placebo [20][21][22][23][24][25][26] or active interventions such as topical clindamycin with benzoyl peroxide, 27 topical benzoyl peroxide alone, 28 topical erythromycin, 29,30 topical minocycline, 31 or tea extract ( Table 2). 32 Seven studies 20,[22][23][24][25][26]31 used oral formulations of zinc sulphate 137 to 300 mg 2 to 3 times daily or gluconate daily.…”
Section: Resultsmentioning
confidence: 99%
“…There were 12 randomized controlled trials and 13 prospective observational studies from 13 countries in Europe, Asia, the Middle East, Africa, and the United States. A total of 12 studies provided data regarding mean serum zinc levels in acne and controls (Table 1), [8][9][10][11][12][13][14][15][16][17][18][19] while 13 studies provided data regarding the efficacy of zinc therapy compared to placebo [20][21][22][23][24][25][26] or active interventions such as topical clindamycin with benzoyl peroxide, 27 topical benzoyl peroxide alone, 28 topical erythromycin, 29,30 topical minocycline, 31 or tea extract ( Table 2). 32 Seven studies 20,[22][23][24][25][26]31 used oral formulations of zinc sulphate 137 to 300 mg 2 to 3 times daily or gluconate daily.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the high prevalence of acne and the known relevance of nutrition with acne, studies on their association are relatively scarce. A limited number of nutritional studies has found with a number of nutrients including vitamin E, zinc, vitamin A (Ozuguz et al, 2014;El-Akawi et al, 2006), selenium (Michaëlsson, 1990), and copper (Ikaraoha et al, 2017) deficient in acne patients. This deficiency could either partly play a role in triggering acne or be the effect of acne pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike vitamin E studies, there are a good number of studies on zinc level in acne patients though the findings varied (Ozuguz et al, 2014;Ikaraoha et al, 2017;Nasiri et al, 2009;Mogaddam et al, 2014;Kaymak et al, 2007;Michaëlsson and Ljunghall, 1990;Michaëlsson, 1990). While both of the studies on the Turkish population found significant zinc deficiency in acne patients (Ozuguz et al, 2014;Kaymak et al, 2007), other studies on patients from Iran (Nasiri et al, 2009;Mogaddam et al, 2014) and Nigeria (Ikaraoha et al, 2017) found no significant difference when compared to the healthy volunteers in coherence to this study. The study of El-Dibany and Elhassi (2019) also reported no correlation between serum zinc level and severity of acne.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations